Giant Cutaneous Horn - Gupta Shally; Thappa Devinder M; Singh Sirisha; Sethuraman Gomathy; Ratnakar Chaganti (Wolters Kluwer Medknow Publications, 2000)
A case of giant cutaneous horn arising over verruca vulgaris on the chest is reported